Hesperetin conjugated PEGylated gold nanoparticles exploring the potential role in anti-inflammation and anti-proliferation during diethylnitrosamine-induced hepatocarcinogenesis in rats - Gokuladhas Krishnan; Jayakumar Subramaniyan; Pramila Chengalvarayan Subramani; Barath Muralidharan; Devaki Thiruvengadam (Elsevier, 2017)
Liver cancer is the fifth most common cancer and one of the leading causes of death in the world, and second most common cause of death in men. Natural products emerge as the most enduring approaches in the development of anticancer targeting drug. Hesperetin (HP), one of the abundant flavonoids found naturally in citrus fruits, has received considerable attention in anti-cancer promotion and progression. The present study was conducted to decipher the role of 0.5 ml hesperetin conjugated gold nanoparticles (Au-mPEG(5000)-S-HP NPs) during diethylnitrosamine (DEN)-induced hepatocarcinogenesis in male Wistar albino rats and shows the better antioxidant that possesses anti-inflammatory, anti-proliferation and anticarcinogenic properties and may modulate signaling pathways. The confirmation of polymer functionalized gold nanoparticles and drug loaded polymer gold nanoparticles were characterized by HR-TEM with EDAX, and DLS with Zeta potential techniques. The drug encapsulation efficiency and release properties were carried out in PBS at pH 7.4 for Au- mPEG(5000)-S-HP and compared with the control pure hesperetin (HP). Here, we review the role of mast cell counts, tumor necrosis factor alpha (TNF-α), transcription factor nuclear factor-κB (NF-κB), levels of glycoconjugates, proliferating cell nuclear antigen (PCNA) and argyrophilic nucleolar organizing regions, are the master regulator of inflammation and proliferation, in the development of hepatocellular injury, liver fibrosis and HCC. DEN-administered animals showed increased mast cell counts, tumor necrosis factor alpha, transcription factor nuclear factor-κB, glycoconjugates, proliferating cell nuclear antigen, and argyrophilic nucleolar organizing regions. Whereas Au-mPEG(5000)-S-HP NPs supplementation considerably suppressed all the above abnormalities. These results suggest that the Au-mPEG(5000)-S-HP NPs exhibited the better potential anticancer activity by inhibiting cell inflammation and proliferation in DEN-induced hepatocellular carcinogenesis.